Neuroprotective Effects of Glycyrrhiza glabra Total Extract and Isolated Compounds - Ali O. E. Eltahir; Sylvester I. Omoruyi; Tanya N. Augustine; Robert C. Luckay; Ahmed A. Hussein (MDPI AG, 2024)
Glycyrrhiza glabra L. is a plant commonly utilized in herbal medicine and stands out as one of the more extensively researched medicinal plants globally. It has been documented with respect to several pharmacological activities, notably, neuroprotective effects, among others. However, the neuroprotective activity of pure phenolic compounds has not been reported yet. The chromatographic of a methanolic extract yielded twenty-two compounds, viz.: naringenin 4'-O-glucoside (1), 3',4',7-trihydroxyflavanone (butin) (2), liquiritin (3), liquiritin apioside (4), abyssinone (5), glabrol (6), isoliquiritin (7), neoisoliquiritin (8), isoliquiritin apioside (9), licuraside (10). 3'[O], 4'-(2,2-dimethylpyrano)-3,7-dihydroxyflavanone (11), glabrocoumarin (12), glabrene (13), isomedicarpin (14), 7-hydroxy-4'-methoxyflavone (formononetin) (15), ononin (16), glycyroside (17), (3S)-7,4'-dihydroxy-2'-methoxyisoflavan (18), glabridin (19), neoliquiritin (20), 3,11-dioxooleana-1,12-dien-29-oic acid (21), and 3-oxo-18β-glycyrrhetinic acid (22). The results of the neuroprotection evaluation showed that G. glabra total extract (TE) and compounds 1, 7, 11, 16, and 20 protected SH-SY5Y cells by inhibiting the depletion of ATP and elevated caspase 3/7 activities induced by MPP+. Indeed, this study reports for the first time the structure and activity of compound 11 and the neuroprotective activity of some phenolic constituents from G. glabra.